Perfil de participantes do projeto Hidroterapia, exercícios aeróbios e alongamento no tratamento de portadores de fibromialgia - Barros, Thamyres Rangel Mendes [UNESP] (2015)
Introduction: Fibromyalgia is a rheumatic syndrome related to the presence of tender points at specific locations of the body. Despite having no specific cause has to do with psychological disorders after physical and emotional trauma. Objective: The objective of the study is to analyze the profile of patients participating in fibromyalgia that treat the project “Hydroterapy, aerobic exercise and stretching to treat fibromyalgia patients”. Methods: To obtain the profile of the participants have used the questionnaire QIF, the Tender points and Body Mass Index. Results: The sample consisted of 10 women with an average age of 51,30±14,90 years overweight. The tender points are an average of 12,40 ± 4,06, and the areas of the QIF had a negative score for items such as fatigue, morning tiredness, stiffness, anxiety and depression. Conclusion: The results showed that the participants, mostly present functional and emotional limitations that must be minimized during treatment thus enabling a better quality of life.